A 3D reconstruction method based on RGB-D camera. Issue 4 (March 2021) - Zhu, Fan; Li, Shaobin; Guo, Xiaohan
Abstract: 3D surface reconstruction with realistic feeling is a hot research field in computer graphics. In order to reconstruct 3D models with high precision, a 3D reconstruction method is proposed in this paper.Based on the BundleFusion reconstruction algorithm, this method uses color images and depth images of indoor scenes obtained by Intel's realsenseD435i depth camera for rapid 3D reconstruction.An improved ORB feature detection algorithm is used for image feature extraction, and the efficiency of several classical feature detection algorithms in image matching is compared.Experiments show that this method can effectively generate 3d models with higher precision and better sense of reality.